1957
DOI: 10.1139/o57-011
|View full text |Cite
|
Sign up to set email alerts
|

On the Antigenicity of Insulin

Abstract: On the basis of body weight, mice showed a higher percentage survival to large doses of insulin than did rabbits and these in turn were more resistant to insulin than guinea pigs. Antibodies to insulin were induced in five species of animals. Anti-insulins produced by the guinea pig, rabbit, sheep, and horse can each neutralize insulin extracted from the pancreas of the rabbit, sheep, horse, pig, ox, and monkey (Macacus rhesus), but none of the four can neutralize insulin extracted from guinea-pig pancreas. Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

1960
1960
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 1 publication
1
23
1
Order By: Relevance
“…The majority of our deaths were directly due to haemorrhage following cardiac puncture and some were probably caused by intercurrent infections. In other respects, however, our experiences are similar to those of Moloney & Goldsmith (1957), from whose results it was concluded that serum with an insulin-neutralizing potency of about 0-8 u./ml. might be expected from most animals injected at monthly intervals with 20-50 u. insulin and bled 10-20 days later.…”
Section: Discussionsupporting
confidence: 82%
“…The majority of our deaths were directly due to haemorrhage following cardiac puncture and some were probably caused by intercurrent infections. In other respects, however, our experiences are similar to those of Moloney & Goldsmith (1957), from whose results it was concluded that serum with an insulin-neutralizing potency of about 0-8 u./ml. might be expected from most animals injected at monthly intervals with 20-50 u. insulin and bled 10-20 days later.…”
Section: Discussionsupporting
confidence: 82%
“…In view of previous work by others (for references see Wright, 1960) and especialiy that of Moloney and his co-workers (Moloney & Coval, 1955; Moloney & Goldsmith, 1957;Moloney & Aprile, 1959) it seems reasonable to conclude that the transient hyperglycaemia provoked in the rat, cat and rabbit by the injection of guinea-pig anti-insulin serum is due to the neutralization of their endogenously secreted hormone by insulin antibodies which are not species-specific. Although we have failed to demonstrate the disappearance of insulin from the blood, one of us (Wright, 1959a) has shown that, in vitro, serum from some of the insulin-treated guinea-pigs used in the present experiments will abolish the stimulant effect of various insulins upon glucose consumption by the isolated rat diaphragm, but not that of synthetic hypoglycaemic agents such as synthalin and phenethyldiguanide.…”
Section: Discussionmentioning
confidence: 83%
“…It is now generally recognized that anti-insulin serum obtained from guinea pigs immunized with beef insulin does not serve to identify a specific molecule with insulin activity; the antiserum reacts with insulins exhibiting considerable structural differences (32)(33)(34)(35)(36) but is still available to the isolated normal rat adipose tissue. After extraction with acid ethanol, however, some effectiveness on the rat diaphragm is unmasked, and partial neutralization by antiinsulin can be shown.…”
Section: Discussionmentioning
confidence: 99%